Competitive balance in the English Premier League. Issue 1 (2nd January 2019) - Penn, Roger; Berridge, Damon
Abstract: The paper explores competitive balance in the top tier of English league football during the era of the Premier League. This era is compared with both the preceding twenty-five year period and also with the era before World War I. Using several statistical measures, the analysis shows that the current high levels of competitive imbalance are not new phenomena. An explanation is proffered in terms of unequal resources between clubs which are inherent to the 'longue durée' of professional league football in England.